Glycosylation markers for cancer diagnosing and monitoring - Dwek, R; Hamid, U; de Llorens, R; Peracaula, R; Radcliffe, C; Robertson, J; Royle, L; Rudd, P; Zitzmann, N (World Intellectual Property Organization, 2006)
One can identify and quantify one or more glycosylation markers of cancer by utilizing quantitative HPLC analysis of glycans which have been released from unpurified glycoproteins. The unpurified glycoproteins can be total glycoproteins or a selection of the total glycoproteins. The identified glycosylation marker can be a native glycan or a digestion product which has been segregated and amplified by exoglycosidase digestions. One can utilize the identified glycosylation marker, for example, for diagnosing and/or monitoring cancer in a subject. One can also use the glycosylation marker to identify glycoprotein biomarkers that carry the glycosylation marker. Such biomarkers can also be used for monitoring and/or diagnosing cancer. The biomarker may also be a subset of glycoforms of a glycoprotein that are separated in trains of spots on 2D gel.